The estrous cycle modulates rat caudate-putamen medium spiny neuron physiology - Willett, Jaime A. (Eur J Neurosci, 2019)
The neuroendocrine environment in which the brain operates is both dynamic and differs by sex. How differences in neuroendocrine state affect neuron properties has been significantly neglected in neuroscience research. Behavioral data across humans and rodents indicate that natural cyclical changes in steroid sex hormone production affect sensorimotor and cognitive behaviors in both normal and pathological contexts. These behaviors are critically mediated by the caudate-putamen. In the caudate-putamen, medium spiny neurons (MSNs) are the predominant and primary output neurons. MSNs express membrane-associated estrogen receptors and demonstrate estrogen sensitivity. However, how the cyclical hormone changes across the estrous cycle may modulate caudate-putamen MSN electrophysiological properties remains unknown. Here, we performed whole-cell patch clamp recordings on male, diestrus female, proestrus female, and estrus female caudate-putamen MSNs. Action potential, passive membrane, and miniature excitatory postsynaptic current properties were assessed. Numerous MSN electrical properties robustly differed by cycle state, including resting membrane potential, rheobase, action potential threshold, maximum evoked action potential firing rate, and inward rectification. Strikingly, when considered independent of estrous cycle phase, all but one of these properties do not significantly differ from male MSNs. These data indicate that female caudate-putamen MSNs are sensitive to the estrous cycle, and more broadly, the importance of considering neuroendocrine state in studies of neuron physiology.